Language, Identity, and Ethics in AI-Driven Art: Perspectives from Human Artists in Digital Environments - Torres, Aira Jenica; C. Alberto, Jasper Mareece; J. Guieb, Angel Pearl; DR. Paray, Ayessa; A. Villarama, Joseph (WISE Pendidikan Indonesia, 2025)
The rise of artificial intelligence (AI) in the creative industries has sparked significant debates on its ethical, economic, and sociocultural implications. This study delves into the narratives of human artists grappling with the advent of AI-generated art, focusing on its impact on creativity, cultural identity, and the artistic community. Employing a qualitative phenomenological approach, the research gathered insights from eight artists through in-depth semi-structured interviews. Thematic analysis revealed three key concerns: economic challenges such as job displacement and income instability, ethical dilemmas surrounding originality and copyright, and the devaluation of human creativity. Despite these challenges, artists expressed diverse responses to AI, ranging from fear of obsolescence to embracing AI as a tool for collaboration and innovation. Further, the study examines the role of AI in reshaping digital communication patterns and how it influences the sociocultural dimensions of art in digital media environments. Findings highlight the duality of AI as both a threat and a creative partner, underscoring the urgent need for ethical guidelines and regulatory frameworks to address these challenges. This research contributes to the broader discourse on AI’s role in shaping creative industries and cultural authenticity, advocating for a balanced integration of AI that preserves the irreplaceable value of human creativity and identity.